A review of neosporosis and pathologic findings of Neospora caninum infection in wildlife. Issue 2 (August 2015) - Donahoe, Shannon L.; Lindsay, Scott A.; Krockenberger, Mark; Phalen, David; Šlapeta, Jan
Highlights: The importance of Neospora caninum -associated disease in wildlife is reviewed. There are only 12 reports of clinical neosporosis in wildlife species to date. The best practice guidelines to follow for reporting wildlife cases of neosporosis are presented. Graphical Abstract: Abstract: Neospora caninum is an apicomplexan parasite that is the etiologic agent of neosporosis, a devastating infectious disease regarded as a major cause of reproductive loss in cattle and neuromuscular disease in dogs worldwide. This protozoan pathogen is maintained in the environment by a heteroxenous life cycle that involves a definitive canid host and a wide range of intermediate hosts. In recent years, a number of wildlife species have been investigated for their possible involvement in the N. caninum life cycle and many have been implicated as intermediate hosts. However, in many instances these studies have utilized serological and molecular techniques to detect infection in clinically normal animals, and investigation of possible associated morbidity, mortality, and pathology has been neglected. As such, the occurrence and importance of Neospora -associated disease in wildlife species are unknown. In order to improve our understanding of the significance of N. caninum infection in nondomestic species, the present review provides an up-to-date summary of clinical neosporosis and N. caninum- associated pathologic lesions in naturally and experimentally infected wildlife species. We provide a list of all free-ranging and captive wildlife species identified with N. caninum infection to date using currently available diagnostic tools. The advantages and disadvantages of diagnostic methods in wildlife are addressed in order to recommend optimal diagnosis of confirming N. caninum infection and neosporosis in nondomestic species. Although current data would suggest that N. caninum infection does not adversely impact wildlife populations, there is a need for greater international uniformity in the diagnosis of N. caninum infection and neosporosis in nondomestic species in order to assess the true consequences of parasite infection.